Layout and Design of Dental Clinics During the Covid19 Pandemic - Jusuf Kristianto; Adinda Nur Amaliah; Ita Astit; Adelina Barus (Syntax Corporation Indonesia, 2023)
The Coronavirus Disease (COVID-19) pandemic has occurred since March 2020. Dentists and dental therapists have a very high risk of transmitting the SARS-CoV-2 virus. Dentists and dental and oral therapists are not spared from this virus because transmission can be through the release of aerosols or droplets containing the virus or direct contact with mucous membranes, oral fluids, and instruments and surfaces contaminated with the virus. For this reason, an appropriate layout and design approach is needed to avoid these aerosols or droplets. Objective: to get an overview of the Layout and Design of a Dental Clinic that is responsive to the spread of the virus during the Covid-19 Pandemic at a Private Dental Clinic in the Jakarta Region 2022.Methods: This research is a descriptive study with a sample of 30 private dental clinics in the South Jakarta area using random sampling technique. Results: The results showed that private dental clinics in the South Jakarta area which had complete availability of complementary equipment 10 clinics (33.3%), 17 clinics (56.7%) were incomplete, 3 clinics (10%) were incomplete, compliance with the location and design as well as the percentage of complementary tools that are very suitable, appropriate, and not suitable are the same, namely (26.7%) and (20%) are not very suitable, the air flow is in accordance with the PDGI guidelines, namely (36.7%), (3 ,3%) is not suitable, and (60%) is not suitable. Conclusion: Most of the private dental clinics in the South Jakarta area have, the layout of the complementary equipment according to the PDGI guidelines, the criteria are very suitable, still less than 1/3 of the number of respondents and 1/5 of the number of respondents who are not very suitable, complementary tools are incomplete and some large has inappropriate airflow.